Obtaining a Set of Recommendations for Evolving Executable Languages towards Systems-of-Systems Architecture Design - Lebtag, Bruno G. A.; Graciano Neto, Valdemar Vicente (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2020: Anais Estendidos do XI Congresso Brasileiro de Software: Teoria e Prática, 2020)
Systems of Systems (SoS) are complex systems composed of managerially and operationally independent constituent systems (CS). Smart cities are examples of SoS. However, these types of systems impose challenges to traditional software architecture such as highly evolutionary architecture due to the evolution of individual CS and emergent behaviors that results from the interoperability of CS. Executable Models (ExM) are a class of models that can be executed and that can assist on architectural design of SoS. By using them, architects can predict the SoS structure and behavior by visualizing and simulating the SoS still at design-time. On the other hand, as any other emergent technologies, it suffers with absent scientific evidences of its benefits, mainly in industrial context. The main contribution of this master thesis project intends to be the presentation of evidences about the use of ExM to solve problems in the SoS software architecture design. For achieving such purpose, this project is structured in well-defined steps: (i) a systematic mapping study, (ii) elaboration of a conceptual map derived from the mapping study, (iii) a survey to obtain perceptions from software engineering professionals on the use of ExM in the context of engineering simple systems and (iv) a new survey expanding the previous study and to obtain perceptions from software engineering professionals on the use of ExM in the context of architectural design of SoS. Preliminary results reveal that ExM have been reported in diverse SoS domains, offering a dynamic and interactive view to the SoS. We also found that software engineering professionals see ExM as suitable solution for dealing with complex and critical systems as SoS.